Validation of the name Oenothera italica (Onagraceae) - Woźniak-Chodacka, Monika (Phytotaxa, 2019)
Oenothera italica Rostański & Soldano (1981: 376) (sect. Oenothera subsect. Oenothera) is one of about 100 taxa of the genus Oenothera Linnaeus (1753: 346) which have been formally recognized in Europe (Hudziok 1968, Soldano 1993, Rostański in Rostański et al. 2004, 2010). The species was described from Italy by Rostański and Soldano (1981) and assigned later to the typical series Oenothera by Rostański (1985). However, its name was not validly published because two different gatherings were indicated as syntypes. I have searched for a proper typification in several relevant sources (e.g. Soldano 1993, Rostański et al. 2004, Rostański et al. 2010), with no success.